GAMBARAN PENGETAHUAN ORANGTUA TENTANG PERTUMBUHAN GIGI DAN PENCEGAHAN KARIES GIGI - Noorrahma Nova Hidayah; Nining Ningrum; Tiurmina Sirait; Dewi Sodja Laela (Poltekkes Kemenkes Bandung, 2022)
Parents' knowledge about the period of tooth growth, both primary and permanent teeth, is very important, but in fact, parents often don't care about their children's teeth. The role of parents is very necessary for guiding, providing understanding, reminding, and providing facilities to children so that children can maintain oral hygiene. Parents also have an important role in preventing caries in children. This study aims to describe the knowledge of parents about dental growth and prevention of dental caries in TK Kemala Bhayangkari 42 Bandung. This type of research uses descriptive research methods. The place and time of this research were carried out at Kemala Bhayangkari 42 Kindergarten, Bandung City. The population in this study were all parents of Kemala Bhayangkari 42 Kindergarten students in Bandung, amounting to 35 people. The research sample is total sampling and the research instrument uses a questionnaire. Parents' knowledge of dental growth in the less category is 51.4% and the level of parental knowledge about caries prevention is in the sufficient category, which is 48.6%. Parental knowledge about dental growth is still in the poor category, while parental knowledge about caries prevention is in the sufficient category.